Helium and argon cold plasma effects on the 4T1 cancer cells and a triple negative mouse model of breast cancer - Mahdiyeh Bakhtiyari-Ramezani; Meysam Nasiri; Mansoureh Baniasadi (Scientific Reports)
Abstract Nowadays, cold atmospheric plasma (CAP) technology has developed as an innovative tool for cancer therapy. Although many studies have reported the antitumor effects of plasma in vivo and in vitro, there are many challenges, including standardization of plasma devices and treatment time for different tumors. For the first time, we aimed to evaluate and compare optimal exposure time and direction-dependent cellular effects of helium and argon plasma on the 4T1 cancer cells and a triple-negative mouse model of breast cancer. This study used two types of helium and argon plasma jet devices with different input parameters. In vitro evaluations on 4T1 cell line using the MTT assays and flow cytometry analysis demonstrate CAP-induced apoptosis in all treated groups, especially in the direct approach. These changes were concurrent with increased intracellular reactive oxygen species levels and decreased total antioxidant capacity in these cells. In vivo studies concurrent with in vitro results revealed that CAP therapy reduces tumor size, decreases Nottingham histological score, prevents weight loss, and increases the survival rate in all treated groups. These results suggest that plasma therapy may overcome the adverse effects of approved cancer therapeutic strategies and seems to be a significant issue for cancer patients in the clinical stage, alone or in combination with current therapeutic programs.